Essays in fiscal federalism - Musgrave, Richard A. (Washington, D.C. : The Brookings Institution, 1965)
The book deals with fiscal federalism and multi-unit public finance based on the dissertations prepared under the sponsorship of Brookings Institution's program in Government Finance.
Includes bibliographical references and index.
gp 22/01/2019
Loans
Keywords: Intergovernmental fiscal relations; Fiscal policy; Finance, Public